Analisis Kinerja Penyuluh KB pada Dinas Pemberdayaan Perempuan Perlindungan Anak dan Keluarga Berencana (DP3AKB) Kota Serang - Hasanah, Neisa Nisatul; Stiawati, Titi (Publikasi Penelitian Terapan dan Kebijakan, 2024)
The Bangga Kencana program is one of the BKKBN programs carried out in Serang City. Family planning instructors provide guidance and counseling regarding the golden pride program to the community. The aim of this research is to see the performance of family planning instructors in Serang City. Data collection was carried out through observation and interviews. This research uses a qualitative method with a descriptive approach. The research results show that the performance of family planning instructors in Serang City is good in terms of time utilization and performance agreements related to abilities and techniques carried out during KIE, completion of reports and responsibility for completing targets. The obstacle to the performance of family planning instructors is the limited number of family planning instructors compared to the number of sub-districts in Serang City.